Restoring confidence in troubled financial institutions after a financial crisis - Calomiris, Charles W.; Carlson, Mark (Journal of Financial Intermediation, 2023)
After an unprecedented number of banks suspended operations in the during Panic of 1893, the head regulator of banks chartered by the United States government allowed about 100 banks to reopen after certifying their solvency. We evaluate whether actions by bank owners to change management, contract with depositors to extend liability maturity structure, write off bad assets, and/or inject capital affected bank survival and deposit retention. This historical episode is particularly informative because there was no expectation of government intervention. We find that contracting with depositors provided short-term benefits while dealing with bad assets was key for long-run viability.